(untitled) (Ameghiniana, 2014)
The Ostracoda recovered from sediments of the Cerro de la Gloria and Canal 18 Members of the Las Escobas Formation, at three outcrops (CI5, KMI and KM2) of the northeastern region of Buenos Aires Province, are analized. Qualitative and quantitative evaluations of the fauna are made in order to obtain palaeoenvironmental inferences. Section CI5 contains marine littoral and sublittoral Ostracoda. Combined analyses of the qualitative information and the quantitative parameters, together with sedimentological evidence, allows the inference of littoral and sublittoral marine palaeoenvironments, particularly in the foreshore and upper shoreface zones successively. Section KM 1 contains euryhaline, mesohaline and lirnnic Ostracoda; the strata represent an environment of very low energy and the final phase of a marsh repletion. Hypoxic levels are registered, probably as a consequence of the accumulation of organic matter which also brought about partially reducing conditions. In the section KM2, both Members - Cerro de la Gloria and Canal 18- are exposed; it contains Ostracoda whose nature, along the succession, indicates transitional marine environments, partially restricted for the Cerro de la Gloria Member and totally restricted and in part reducing features for the Canal 18 Member. In the case of the deposits of the Cerro de la Gloria Member, a washover sub-environment, associated with a system of barrier islands is proposed; they represent lagoon deposits. The upper section, attributed to the Canal 18 Member of Las Escobas Formation, on the basis of its lithology, colour and structures, in conjunction with the ostracod analysis, indicates that the stratabelong to the final filling phase of a lagoon, most probably a marsh; a decrease in the pH values also accounted as evidenced by the scarcity of ostracods, adults and juveniles, caused by the increment of the environmental deterioration and the restricted conditions.